The Effects of the Quincke Spinal Needle Bevel Insertion on Postdural Puncture Headache and Hemodynamics in Obstetric Patients - Salik, Fikret (Anesth Essays Res, 2018)
AIM: Spinal anesthesia is a widely used procedure in modern anesthesia. Although it is a reliable and frequently used anesthetic procedure, it involves complications, including postdural puncture headache caused by arachnoid punctured, which significantly affects postoperative well-being. In this study, we aimed to observe headache frequency with 26-G Quincke spinal needle in either transverse or sagittal planes. MATERIALS AND METHODS: One hundred patients with American Society of Anesthesiologists status classes I and II who were scheduled for elective cesarean delivery with no contraindications for performing spinal anesthesia were randomly divided into two groups: Group I (transverse n = 50) and Group II (sagittal n = 50). Spinal anesthesia was performed with a 26-G Quincke needle, using 1.5–2.0 ml 0.75% hyperbaric bupivacaine. The anesthesiologists' experience, number of attempts for spinal anesthesia, volume of fluid administered preoperatively and intraoperatively, intervertebral space where spinal anesthesia was administered, and patient movements during the attempts were recorded. Mean arterial pressure and peak heart rates were recorded for 60 min intraoperatively and postoperatively. Headache and back pain complications were observed for 1 week postoperatively. Chi-square tests and statistical comparisons of the rates (statistical significance, P < 0.05) were used for assessments. RESULTS AND CONCLUSIONS: No significant differences were observed with respect to age, height, weight, headache, or incidence of back pain. No significant differences were observed for the number of spinal attempts, intervertebral space where spinal anesthesia was administered, experience of the anesthesiologists, patient movements during the attempts, volumes of fluid administered preoperatively and intraoperatively, or low back pain incidence. Significant reductions in mean arterial pressure were observed between groups after 10, 15, 30, 40, and 50 min. No significant differences were observed in headache or back pain frequency with 26-G Quincke spinal needle in either transverse or sagittal planes. Hypotension was frequently observed in the transverse group.